Ancient Greek civilization - McInerney, Jeremy 1958-; Teaching Company (Chantilly, Virginia The Teaching Company, 1998)
Lectures on Greek history from the late Bronze Age to the time of Alexander the Great, concentrating on the period from 600 to 400 B.C.
Disc 1 : 1. Greece and the western world -- 2. Minoan Crete -- 3. Schlimann and Mycenae -- 4. The long twilight -- 5. The age of heroes -- 6. From Sicily to Syria : 7. Delphi and Olympia -- 8. The Spartans -- 9. Revolution -- 10. Tyranny -- 11. The origins of democracy -- 12. The Persian empire : 13. The Persian wars -- 14. The Athenian empire -- 15. The art of democracy -- 16. Sacrifice and Greek religion -- 17. Theater and the competition of art -- 18. Sex and gender : 19. The Peloponnesian war, part 1 -- 20. The Peloponnesian war, part 2 -- 21. Socrates on trial -- 22. Slavery and freedom -- 23. Athens in decline -- 24. Philip, Alexander, and Greece in transition.
Lecturer: Jeremy McInerney, University of Pennsylvania.
Lecture transcript and course guidebook published to accompany DVD and and videotapes with the same title.
Keywords: Gods, Greek; Art, Greek -- History; Sex -- Greece; Philosophers -- Greece; Greece -- History -- To 146 B.C.; Greece -- Civilization -- To 146 B.C.; Greece -- History -- Persian Wars, 500-449 B.C.; Greece -- Politics and government; Greece -- Religion